أشكال توظيف التّراث الشّعبي في الرّواية الجزائرية ـ نماذج مختارة (El-Wahat Journal for Research and Studies, 2023)
ملخص:تسعى هذه الورقة العلمية إلى البحث في تلك الكتابات الصادرة عن أقلام جزائرية أبت إلّا أن تشتغل على توظيف التّراث الشّعبي داخل المتون الحكائية، ساعية إلى التّغيير والخوض في غمار التّجريب بما امتلكت من زمام تشرّب التّراث الذي يعتبر السّبيل القويّ الذي يؤثّرون به، فكانت كتاباتهم مؤثّرة جدا في أوساط القرّاء، بما قدّموه من منجزات روائية ذات صبغة تراثية شعبية، لذلك ارتأينا اختيار نماذج روائية لتكون محطّ الدراسة والتحليل.لنصل في الأخير إلى أنّ الرّواية الجزائرية بصنفيها (الرّجالية والنّسائية) عالم كبير يوطّن داخله عالما أكبر وهو التّراث الشّعبي بنتاجيه (الشّعري والسّردي)، فما احتوته هذه الرّوايات يبدو في ظاهره عاديا، لكن بعد الدراسة والتمحيص يتبيّن أنّه محمّلا بالأنساق الثقافية الرامزة والهادفة إلى مقصديات خطابية معيّنة. كلمات دالة : الأشكال، التجلّيات، التّراث الشّعبي، الرّواية الجزائرية، النّتاج الشّعري والسّردي. Abstrac: This scientific paper seeks to search for those writings issued by Algerian pens that decided to work on employing the popular heritage within the narrative texts, seeking to change and delve into the midst of experimentation with what it possessed of the reins of imitating the heritage, which is the powerful way that they influence, so their writings were very influential. in the circlesReaders, with their fictional achievements of a popular heritage character, so we decided to choose fictional models to be the focus of study and analysis.In the end, let us conclude that the Algerian novel in its two genres (men and women) is a large world that resides within it a larger world, which is the folklore with its two products (poetic and narrative). specific.Key words: forms, manifestations, folklore, Algerian novel, poetic and narrative production.